Proximal isolated congenital anterior urethrocutaneous fistula resulting in a urethral “skip” lesion - Shane F. Batie; Caitlin T. Coco; Micah A. Jacobs (Urology Case Reports, 2022)
Urethrocutaneous fistula is an unfortunate but well recognized complication of hypospadias repair surgery and traumatic injury to the penis. Congenital anterior urethrocutaneous fistula of the male urethra is an exceedingly rare phenomenon, with approximately 50 cases being reported in the literature. We report a case of proximal isolated congenital anterior urethrocutaneous fistula at the penoscrotal junction.